Effect of pulse energy, frequency and length on holmium: yttrium-aluminum-garnet laser fragmentation efficiency in non-floating artificial urinary calculi - Wezel, Felix; Häcker, Axel; Gross, Andreas; Michel, Maurice Stephan; Bach, Thorsten (Journal of endourology, 2010)
Background and Purpose: Holmium:yttrium-aluminum-garnet (Ho:YAG) laser lithotripsy is the standard lithotrite in ureteroscopy. We investigated the influence of pulse frequency, energy and length on the fragmentation efficiency of Ho:YAG laser lithotripsy in non-floating artificial stones in vitro. - - Materials and Methods: Stone fragmentation efficiency of three different Ho:YAG laser devices were evaluated in vitro at different pulse energy (1.0 and 2.0 J) and frequency settings (5 and 10 Hz), resulting in a standardized output power of 10W, respectively. Where possible, pulse length was modified (350 vs 700 μsec). Each setting was performed with a 273 μm and a 365 μm fiber. Lithotripsy was conducted using non-repulsive stones consisting of soft stone (plaster of Paris) and hard stone composition (Fujirock type 4). - - Results: Our results showed an increased stone disintegration efficiency at higher pulse energy (2.0 J/5 Hz vs 1.0 J/10 Hz) independently of two fiber diameters and stone types applied in this study (P < 0.05 in 18 of 20 groups). Similarly, reduction of the pulse length from 700 to 350 μsec resulted in a higher stone disintegration (P < 0.05 in 13 of 16 groups). This effect was most prominent when applied to soft stones. Higher fiber diameter was not constantly associated with an increase in stone disintegration. - - Conclusion: We demonstrate that an increase of pulse energy and a reduction of pulse length at a standardized output power of 10W can improve Ho:YAG laser fragmentation efficiency in vitro in nonfloating stones. These results may potentially affect clinical practice of Ho:YAG laser lithotripsy in impacted or large stones, when retropulsion is excluded.